Recovery of Acacia auriculiformis from fire damage - Ab Shukor, Nor Aini (Elsevier, 1993)
An assessment of damage and recovery of Acacia auriculiformis in a provenance trial at the Universiti Pertanian Malaysia was undertaken following an accidental surface fire. The results showed significant differences (P < 0.05) between provenances in their ability to recover vegetatively after being affected by different levels of foliage scorch, with the 1hr. S. Balamuk (16103) provenance being the best. The ability to resprout is possibly a result of the insulating properties of the bark, which protects the dormant buds present underneath it. The results provide a basis of selection of suitable provenances for future breeding for fire resistance and for fire management and silvicultural treatments of this species.